PELATIHAN OPENOFFICE.ORG BAGI GURU SMP SEBAGAIANTISIPASI MAHALNYA PENGGUNAAN MS OFFICE - Supardi, - (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2012)
There four reasons why OpenOffice.org (OOo) should be introducedto the educators at Junior high School. Firstly, Ooo is the great software.OOo is the software developed for 20 years and designed as integratedoffice software that has consistence. Secondly, OOo version 3.3 is very easyto use. The most of educators have basics of using Ms Office. Based on theirexperience of using Ms Office, they will never find difficulties in writing,presenting, calculating and drawing with OOo. OOo is also supported byIndonesian language, so it is for beginner, too. Thirdly, OOo can be gotfreely. It means that we can get from anyone, distrubute to every one. OOois released under GPL (General Public Licence) license. Fourthly, OOo isopen. OOo is developed using paradigm open or "˜no secret'. It means thatevery one could see the source codes of this program. Anyone may giveadvices to improve and repaire the bugs. In consideration of economiccondition the most people in Indonesia, OOo gives smart alternative toanticipate the digital devide.